Short-term weight gain velocity in infants with congenital diaphragmatic hernia (CDH). (March 2017) - Gien, Jason; Murthy, Karna; Pallotto, Eugenia K; Brozanski, Beverly; Chicoine, Louis; Zaniletti, Isabella; Seabrook, Ruth; Keene, Sarah; Alapati, Deepthi; Porta, Nicolas; Rintoul, Natalie; Grover, Theresa R.; et al.
Abstract: Background: Appropriate post-natal growth remains a mainstay of therapeutic goals for infants with CDH, with the hypothesis that optimizing linear growth will improve survival through functional improvements in pulmonary hypoplasia. However, descriptions of growth and the effect on survival are limited in affected infants. Objective: Describe in-hospital weight gain related to survival among infants with CDH. Design/methods: Children's Hospitals Neonatal Database (CHND) identified infants with CDH born ≥ 34 weeks' gestation (2010–14). Exclusion criteria were: admission age > 7 days, death/discharge age < 14 days, or surgical CDH repair prior to admission. Weight gain velocity (WGV: g/kg/day) was calculated using an established exponential approximation and the cohort stratified by Q1: < 25%ile, Q2–3: 25–75%ile, and Q4: > 75%ile. Descriptive measures and unadjusted Kaplan-Meier analyses describe the implications of WGV on mortality/discharge. Results: In 630 eligible infants, median WGV was 4.6 g/kg/day. After stratification by WGV [Q1: ( n  = 156; < 3.1 g/kg/day); Q2–3 ( n  = 316; 3.1–5.9 g/kg/day), and Q4 ( n  = 158, > 5.9 g/kg/day)] infants in Q1 had shortest median length of stay, less time on TPN and intervention for gastro-esophageal reflux relative to the other WGV strata ( p  < 0.01 for all). Unadjusted survival estimates revealed that Q1 [hazard ratio (HR) = 9.5, 95% CI: 5.7, 15.8] and Q4 [HR = 2.9, 95% CI: 1.7, 5.1, p  < 0.001 for both] WGV were strongly associated with NICU mortality relative to Q2–3 WGV. Conclusion: Variable WGV is evident in infants with CDH. Highest and lowest WGV appear to be related to adverse outcomes. Efforts are needed to develop nutritional strategies targeting optimal growth. Highlights: Growth velocity during NICU hospitalization is suboptimal for infants with CDH. CDH infants with the longest duration of TPN had improved growth. Highest and lowest growth velocity percentiles are associated with NICU mortality.